2007
DOI: 10.1002/dvg.20351
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of attractin homologs

Abstract: Attractin (ATRN) and Attractin-like 1 (ATRNL1) are highly similar type I transmembrane proteins. Atrn null mutant mice have a pleiotropic phenotype including dark fur, juvenile-onset spongiform neurodegeneration, hypomyelination, tremor, and reduced body weight and adiposity, implicating ATRN in numerous biological processes. Bioinformatic analysis indicated that Atrn and Atrnl1 arose from a common ancestral gene early in vertebrate evolution. To investigate the genetics of the ATRN system and explore potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…The Alp binding motif in Mc4r contains a putative phosphorylation site indicating that Alp might play a role in Mc4r trafficking. Alp knock-out mice appear normal with no alterations in body weight or pigmentation [51]. Further experiments using double mutants over-expressing Agrp and deficient for ALP could elucidate possible interaction of these two proteins in vivo.…”
Section: Mouse Models With Mutations In the Melanocortin Systemmentioning
confidence: 98%
“…The Alp binding motif in Mc4r contains a putative phosphorylation site indicating that Alp might play a role in Mc4r trafficking. Alp knock-out mice appear normal with no alterations in body weight or pigmentation [51]. Further experiments using double mutants over-expressing Agrp and deficient for ALP could elucidate possible interaction of these two proteins in vivo.…”
Section: Mouse Models With Mutations In the Melanocortin Systemmentioning
confidence: 98%
“…ATRN, ATRNL1, and MEGF8 not only share homology in their ectodomains but they are also the only proteins in the mammalian proteome to share a specific motif (MASRPFAXVXV) of unknown function in their cytoplasmic tails (Walker et al, 2007). We recently demonstrated that transgenic overexpression of Atrnl1 can rescue the pigmentation, reduced myelination, and spongiform neurodegeneration phenotypes of Atrn mutant mice despite the fact that Atrnl1 mutants have no discernable phenotypes of their own (Walker et al, 2007). Given the additive effects of dal and Atrn mg-3J on pigmentation and CNS and testicular vacuolation, we mated dal mutants to our Atrnl1 transgenic founder to determine whether overexpression of Atrnl1 could also rescue the phenotypes of dal mutant mice.…”
Section: Overexpression Of Atrnl1 Does Not Rescue Dal Mutant Phenotypesmentioning
confidence: 99%
“…Male and female A y /A; dal/dal, A y /A; dal/1, and A y /A; 1/1 were weighed and measured (snout to base of tail) at 4-5 months of age. Tg(Atrnl1)B4Tmg mice, which express Atrnl1 under control of the human b-actin promoter, were generated and genotyped as previously described (Walker et al, 2007). The Tg(Atrnl1)B4Tmg founder male was mated to C3;CB-dal/dal females and the F1 progeny backcrossed to C3;CB-dal/dal mice to generate dal/dal mice segregating for the transgene.…”
Section: Mice and Genotypingmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also possible that additional molecules may mediate some parts of this interaction. For example, ATRNL1 (attractin-like 1), is an ATRN homolog that has been shown to interact with the C terminus of MC4R (52) and, when overexpressed, can compensate for loss of ATRN (53). However, because loss-of-function mutations in Atrnl1 show no pigmentary or body weight phenotypes (53) its direct role, if any, in melanocortin biology remains unclear.…”
Section: Mgmentioning
confidence: 99%